PENENTUAN LOKASI OUTLET BANK MENGGUNAKAN DIAGRAM VORONOI DENGAN JARAK EUCLID - Nur Indah Aries Permatasri; Kosala Dwidja Purnomo (UNEJ e-Proceeding, 2022)
Banking is an essential element in developing a country that has a role in raising funds to improve the standard of living of many people. Customers who will visit or use products from a bank will consider several factors. One of them is the location factor or so-called FLP. The algorithm for finding the FLP solution is a Voronoi diagram. Determination of the location will be more emphasize the location of the branch because the location of the branch is a place where banking products are traded and bank control. Determination of the location of this branch by using the Euclidean distance method. Determination of this location will use relevant parameters according to the needs and conditions of the bank such as the number of residents in an area. The Voronoi diagram is used to find the closest location based on a set of points in a closed polygon using 31 locations. The places to be used are from 31 sub-districts from the City of Jember. The method used is the Euclidean distance method which is a method of finding the proximity of the distance of two variables that is used to analyze the problem by determining two adjacent location distances. The results of this study are eight sub-districts that have been weighted for each parameter. Keywords: Euclidean Distance, FLP, Voronoi Diagram